VD_FINDINFO HC / 2016 / 743 vom 2. August 2016 - VD Tribunal cantonal (2016)
ASSISTANCE JUDICIAIRE, AVOCAT D'OFFICE, HONORAIRES, RÉDUCTIONEN GÉNÉRAL | 122 al. 1 let. a CPC (CH), 3 al. 2 RAJ, 3 al. 3 RAJ